Algoritma Apriori Untuk Menentukan Pola Gelandangan dan Pengemis - Wirta Agustin; Yulya Muharmi (Ikatan Ahli Informatika Indonesia, 2018)
Homeless and beggar is a living people and at the same time begging in public. bums and beggars are one of the problems in urban areas, with regard to hygiene, order and security issues that can disrupt the stability and development of the city. The city of Pekanbaru grows well and becomes the centers of economic growth, marked by the establishment of offices, shopping centers, transportation facilities, factories, entertainment facilities, which can encourage homeless and beggars to come. Pekanbaru city government has made efforts to handle homeless and beggars intensively, such as curbing, fostering and empowering the community. All efforts undertaken so far are still focused on how the handling of homeless and beggars who already exist in the city of Pekanbaru, has not been made efforts to prevent homeless and beggars. One way that can be done is to determine the pattern of homeless and beggars. To determine the pattern is needed a method. The method used is the Apriori Algorithm, one of the most popular algorithms on data mining techniques. A priori algorithm is used to generate association rules, with an